Understanding Nuances and Commonalities of Job Descriptions (Journal of Training and Development, 2015)
This paper has explored how job descriptions are developed in today’s organizations. As job descriptions are the foundations of jobs, they have to be prepared following certain guidelines. However, organizations follow different formats and put contents in those formats differently. This paper has searched for if there is a common ground in developing job descriptions. The paper is based on secondary sources of data. It compares and contrasts information from the available sources. The paper is an attempt to consolidate the pieces of knowledge that were already there. In doing so, it has also highlighted the gaps found in writing job descriptions which become remarkable avenues for further research. It concludes with the message that organizations can benefit if they follow the common practice of writing job descriptions discussed in the paper.DOI: http://dx.doi.org/10.3126/jtd.v1i0.13093 Journal of Training and Development Vol.1 2015: 67-76